Endoscopic signs of gastroesophageal reflux disease with different hiatal hernias types - Nykonenko, A. O.; Haidarzhi, Ye. I.; Kiosov, O. M.; Никоненко, Андрій Олександрович; Гайдаржі, Євген Іванович; Кіосов, Олександр Михайлович (Запорізький державний медичний університет, 2022)
The aim of the research was to study the endoscopic signs of gastroesophageal reflux disease with the most common hiatal hernia type I and type III. Materials and methods. The examination results of 153 patients with GERD and the most common hiatal hernia type I and type III at the stage of preparation for antireflux surgical treatment were analyzed. The age was 54.5 ± 11.3, there were 48 (31.4 %) men, 105 (68.6 %) women. In Group I – 85 patients with GERD and type I hiatal hernia, in Group II – 68 patients with GERD and type III hiatal hernia. A complete preoperative examination necessarily included endoscopy with chromoendoscopy (mainly NBI or FICE), biopsy from suspicious foci of the gastric mucosa and the lower third of the esophagus followed by histological analysis. Statistical processing and mathematical analysis of the obtained results were performed using the Statistica for Windows 13 (StatSoft Inc., No. JPZ804I382130ARCN10-J). For comparative analysis the arithmetic mean and standard deviation were calculated and presented as M ± s. Differences between groups were assessed using the sub-module “Difference tests” in the module “Basic statistics and tables”. Differences at P < 0.05 were considered statistically significant. Results. In both groups, non-erosive forms of gastroesophageal reflux disease prevailed: 57 (67.1 %) and 39 (57.4 %) patients respectively. Both in Groups I and II, among the erosive forms there were mainly LA A stages of esophagitis – 20 (23.5 %) and 17 (25.0 %). СLE signs of the esophageal mucosa prevailed in Group I – 16 (18.8 %) patients, in Group II – 5 (7.4 %) patients. The proximal edges of the gastric folds, which are visualized in all patients, were considered the reference point for the true esophageal-gastric junction. Complicated course of GERD was noted in both groups of patients. Мета роботи – вивчити ендоскопічні ознаки гастроезофагеальної рефлюксної хвороби при найпоширеніших I та III типах грижі стравохідного отвору діафрагми на етапі підготовки до хірургічного лікування. Матеріали та методи. Обстежили 153 пацієнтів із ГЕРХ і найпоширенішими I та III типами гриж стравохідного отвору діафрагми під час підготовки до лапароскопічної антирефлюксної операції. Середній вік – 54,5 ± 11,3 року, 48 (31,4 %) чоловіків, 105 (68,6 %) жінок. У І групі – 85 пацієнтів із ГЕРХ і грижею стравохідного отвору діафрагми І типу; у ІІ групі – 68 хворих на ГЕРХ і з грижею стравохідного отвору діафрагми III типу. Повне передопераційне обстеження обов’язково передбачало ендоскопію з хромоендоскопією (передусім NBI або FICE), біопсією з підозрілих вогнищ слизової оболонки шлунка та нижньої третини стравоходу, гістологічний аналіз. Cтатистичне опрацювання та математичний аналіз результатів виконали, використавши пакет прикладних програм Statistica for Windows 13 (StatSoft Inc., № JPZ804I382130ARCN10-J). Для порівняльного аналізу розрахували середнє арифметичне та середнє квадратичне відхилення – M ± s. Розбіжності між групами оцінювали за допомогою підмодуля «Диференціальні тести» в модулі «Основні статистики та таблиці». Статистично значущими вважали відмінності при p < 0,05. Результати. В обох групах переважали неерозивні форми ГЕРХ: 57 (67,1 %) та 39 (57,4 %) хворих відповідно у групах. З-поміж ерозивних форм виявляли переважно LA A стадії езофагіту – 20 (23,5 %) та 17 (25,0 %) у І та ІІ групі відповідно. СLE ознаки слизової оболонки стравоходу переважали в І групі – у 16 (18,8 %), у ІІ – у 5 (7,4 %) хворих. Орієнтиром справжнього стравохідно-шлункового з’єднання вважали проксимальні краї шлункових складок, візуалізовані в усіх хворих. Ускладнений перебіг ГЕРХ визначили в обох групах хворих.
Ендоскопічні ознаки гастроезофагеальної рефлюксної хвороби при різних типах грижі стравохідного отвору діафрагми
Nykonenko A. O. - ORCID ID: 0000-0002-5720-2602; Haidarzhi Ye. I. - ORCID ID: 0000-0001-7211-1795; Kiosov O. M. - ORCID ID: 0000-0002-0212-1549.
Keywords: gastroesophageal reflux disease; hiatal hernia; endoscopy digestive system; гастроезофагеальна рефлюксна хвороба; грижа стравохідного отвору діафрагми; ендоскопічні дослідження травної системи